(untitled) (SAARC Journal of Agriculture, 2021)
A study was conducted to evaluate genetic polymorphism in three Sakini chicken populations using random amplification of polymorphic DNA (RAPD) with seven highly polymorphic primers. All populations showed polymorphism with these primers that generates 59 different bands with an average of 8.4 bands per primer with 78.6% polymorphism nature. Primer OPA-16 produced the highest number of polymorphism bands 47 % and the lowest number of bands was produced by the OPA-05 primer 24 %. Differences for genetic distance (D) among populations were significant (P<0.05). A consensus dendogram was therefore developed to show the phylogenetic relationship among the populations. The cluster pattern is well supported by the principle component analysis that also separates all three populations of Sakini chicken into six major groups. The results provide evidence of the applicability of RAPD to determining genetic relatedness within and among different poultry populations and in developing reproducible markers useful in evaluating individual variation in poultry. SAARC J. Agri., 18(2): 115-124 (2020)